First Report of Orange Rust of Sugarcane Caused by Puccinia kuehnii in Colombia - Cadavid, M (Plant disease, 2012)
Symptoms of sugarcane orange rust were first observed in July 2010 on sugarcane (interspecific hybrid of Saccharum L. species) cv. CC 01-1884 planted in the La Cabaña Sugar Mill, Puerto Tejada, Colombia. Morphological features of uredinial lesions and urediniospores inspected with an optical microscope and scanning electron microscopy were distinct from common rust of sugarcane caused by Puccinia melanocephala Syd. & P. Syd., revealing spores identical morphologically to those described for the fungus P. kuehnii (Kruger) E. Butler, causal agent of sugarcane orange rust (1,3). Uredinial lesions were orange and distinctly lighter in color than pustules of P. melanocephala. Urediniospores were orange to light cinnamon brown, mostly ovoid to pyriform, variable in size (27.3 to 39.2 × 16.7 to 21.2 μm), with pronounced apical wall and moderately echinulate with spines evenly distributed. Paraphyses, telia, and teliospores were not observed. Species-specific PCR primers designed from the internal transcribed spacer (ITS)1, ITS2, and 5.8S rDNA regions of P. melanocephala and P. kuehnii were used to differentiate the two species (2). The primers Pm1-F and Pm1-R amplified a 480-bp product from P. melanocepahala DNA in leaf samples with symptoms of common rust. By contrast, the primers Pk1-F and Pk1-R generated a 527-bp product from presumed P. kuehnii DNA in leaf samples with signs of orange rust, confirming the identity as P. kuehnii. The Centro de Investigación de la Caña de Azúcar de Colombia (Cenicaña) started a survey of different cultivars in nurseries and experimental and commercial fields in the Cauca River Valley and collected leaf samples for additional analyses. Experimental cvs. CC 01-1884, CC 01-1866, and CC 01-1305 were found to be highly susceptible to orange rust and were eliminated from regional trials, whereas commercial cvs. CC 85-92 and CC 84-75, the most widely grown cultivars, were resistant. With the discovery of orange rust of sugarcane in Colombia, Cenicaña has incorporated orange rust resistance in the selection and development of new cultivars. To our knowledge, this is the first report of P. kuehnii on sugarcane in Colombia. Orange rust has also been reported from the United States, Cuba, Mexico, Guatemala, Nicaragua, El Salvador, Costa Rica, Panama, Ecuador, and Brazil. References: (1) J. C. Comstock et al. Plant Dis. 92:175, 2008. (2) N. C. Glynn et al. Plant Pathol. 59:703, 2010. (3) E. V. Virtudazo et al. Mycoscience 42:167, 2001